2020
DOI: 10.1158/1535-7163.mct-19-1016
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Adaptations to MEK and CDK4/6 Cotargeting in Uveal Melanoma

Abstract: ◥Frequent GNAQ and GNA11 mutations in uveal melanoma hyperactivate the MEK-ERK signaling pathway, leading to aberrant regulation of cyclin-dependent kinases (CDK) and cell-cycle progression. MEK inhibitors (MEKi) alone show poor efficacy in uveal melanoma, raising the question of whether downstream targets can be vertically inhibited to provide long-term benefit. CDK4/6 selective inhibitors are FDA-approved in patients with estrogen receptor (ER)-positive breast cancer in combination with ER antagonists/aromat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 48 publications
2
14
0
Order By: Relevance
“…Somatic copy-number alteration analyses from more than 3000 specimens have revealed that Ccnd1, Cdk4, Cdk6, and Ccne1 genes were listed in 30 of the most amplified genes associated with cancer, which highlight their potential as anti-cancer therapeutic targets [25,26]. Anti-cancer effects of the CDK4/6 inhibitors such as palbociclib, ribociclib, and abemaciclib in various types of cancers have been documented and these have all underwent phase III clinical trials [27][28][29][30]. Since the canonical pathway of CDK4/6/cyclin D-RB-E2F in the G1 phase is well-defined, we initially anticipated CDK4/6 inhibitor-induced G1 cell cycle arrest or quiescence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…Somatic copy-number alteration analyses from more than 3000 specimens have revealed that Ccnd1, Cdk4, Cdk6, and Ccne1 genes were listed in 30 of the most amplified genes associated with cancer, which highlight their potential as anti-cancer therapeutic targets [25,26]. Anti-cancer effects of the CDK4/6 inhibitors such as palbociclib, ribociclib, and abemaciclib in various types of cancers have been documented and these have all underwent phase III clinical trials [27][28][29][30]. Since the canonical pathway of CDK4/6/cyclin D-RB-E2F in the G1 phase is well-defined, we initially anticipated CDK4/6 inhibitor-induced G1 cell cycle arrest or quiescence in our study.…”
Section: Discussionmentioning
confidence: 99%
“…IACS-010759 is a clinical-grade small-molecule inhibitor of complex I of the electron transport chain [ 32 ]. IACS-010759 has been shown to selectively kill tumor cells that depend on OXPHOS, both in vitro and in preclinical models of human cancers with no cytotoxicity at tolerated doses in normal cells [ 32 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 ].…”
Section: Introductionmentioning
confidence: 99%
“…Dynamic kinome reprogramming in response to CDK4i/6i has been reported in prostate adenocarcinoma (13), superficial spreading melanoma (14), and uveal melanoma (15) that results in therapy resistance via hyperactivation of the MAPK pathway. We next investigated the MAPK pathway following CDK4i/6i in our ALM system.…”
Section: Erk Hyperactivation Drives Intrinsic Cdk4i/6i Resistance Via...mentioning
confidence: 98%